Association of Smoking with Total Oxidant and Antioxidant Levels in Breast Milk - Yildiz, Nesibe; Yilmaz, Adnan (Makara Journal of Health Research, 2022)
Background: Breast milk is a natural food that contains all the fluids, energy, and nutrients necessary for the optimum growth and development of newborns. Smoking is a public health problem that has harmful effects on the mother and baby. This study aimed to examine the association of exposure to smoking with total oxidant status (TOS) and total antioxidant status (TAS) in breast milk. Methods: Healthy mothers without any health problems during their pregnancy and lactation periods were selected as subjects. Eighty-eight milk samples (44 in the smoking group and 44 in the nonsmoking group) were examined. TOS and TAS were analyzed using Rel Assay commercial kits. Results: TAS level was significantly lower in the smoking group than in the nonsmoking group (p < 0.05). TOS level was higher in the smoking group than in the nonsmoking group, although the difference was not statistically significant (p > 0.05). Oxidative stress index (OSI) was significantly higher in the smoking group than in the nonsmoking group (p < 0.05). Conclusions: Exposure to smoking was associated with low TAS and high OSI in breast milk.